Locus of control as a predictor of academic attitudes among secondary school science teacher trainees at a public university in Uganda - Atibuni, Dennis Zami; Ssenyonga, Joseph; Kani Olema, David; Kemeza, Imelda (International Journal of Educational Policy Research and Review, 2017)
A host of factors often determines academic attitudes among learners. This quantitative study using cross-sectional survey design was conducted to establish the prediction effect of locus of control on academic attitudes among secondary school science teacher trainees at a public university in Uganda. Data were collected from a census of 203 students using structured questionnaires comprising a biodata section, Locus of Control Scale and Academic Attitudes Scale. Analysis was done using SPSS, and information was presented in tables and later described. Results showed that the trainees used mainly external locus of control and had generally moderately negative academic attitudes. Locus of control significantly predicted academic attitudes (t = -2.595, p = .010). Further analysis revealed that there was a statistically significant difference in academic attitudes between students originating from rural areas and those from urban areas. It was concluded that the use of external locus of control shifted responsibility of academic issues from the students to other external causes which likely resulted in counterproductive view the science and hence negative academic attitudes among the students.It is recommended that trainees need to be educated before and during pre-service training to appreciate teaching as a noble profession, and that trainees with the right disposition should be selected at entry to preservice training so as to foster the needed changes in science and technology education for national socioeconomic transformation.
Keywords: Locus of control; Attitude; Science teacher; Secondary school; Trainee